Exploring Educational Leadership Styles in Afghanistan’s Higher Education - Amin, Rahimullah (ADA University, 2024)
This qualitative research was conducted to explore educational leadership styles in Afghanistan’s higher education. It explored how deans and faculty members at three different universities defined educational leadership and the leadership styles practiced by the deans. Furthermore, the study researched the faculty and students’s perceptions of the role of leadership in higher education. The findings indicated different definitions of educational leadership in Afghanistan’s context and different leadership styles in which the transactional and transformational styles are dominant. Deans’ views showed they applied a democratic and transformational leadership style. In contrast, faculty members believed that educational leadership in Afghanistan was transactional and the decisions were centralized. Faculty members and students had a positive perception of the role of educational leadership which they considered significant in faculty development, student success, positive learning, and research environment. The research highlights that a common understanding of leadership definitions and practices in the context of Afghanistan’s higher education is required and also recommends leadership development programs.
Keywords: Educational leadership -- Afghanistan.; Higher education -- Administration -- Afghanistan.; Universities and colleges -- Faculty -- Attitudes -- Afghanistan.; College students -- Attitudes -- Afghanistan.